Biohydrometallurgy for Rare Earth Elements Recovery from Industrial Wastes - Laura Castro; María Luisa Blázquez; Felisa González; Jesús Ángel Muñoz (Molecules, 2021)
Biohydrometallurgy recovers metals through microbially mediated processes and has been traditionally applied for the extraction of base metals from low-grade sulfidic ores. New investigations explore its potential for other types of critical resources, such as rare earth elements. In recent times, the interest in rare earth elements (REEs) is growing due to of their applications in novel technologies and green economy. The use of biohydrometallurgy for extracting resources from waste streams is also gaining attention to support innovative mining and promote a circular economy. The increase in wastes containing REEs turns them into a valuable alternative source. Most REE ores and industrial residues do not contain sulfides, and bioleaching processes use autotrophic or heterotrophic microorganisms to generate acids that dissolve the metals. This review gathers information towards the recycling of REE-bearing wastes (fluorescent lamp powder, spent cracking catalysts, e-wastes, etc.) using a more sustainable and environmentally friendly technology that reduces the impact on the environment.